Training and transfer in aging – is pathway overlap really necessary?. Issue 2 (3rd April 2017) - Aisenberg, Daniela; Cohen, Zahira Ziva; Linkovski, Omer
ABSTRACT: Voelker et al. (this issue) discuss how training improves task speed. They suggest two constraints when exploring how training changes cognition through transfer: (1) a link between improved connectivity and response speed and (2) the transfer task should use pathways altered by training. Looking at the literature on aging, we believe the latter constraint should be reconsidered. We discuss evidence from developmental aging, questioning whether the transfer task necessarily requires using training task pathways. Additionally, we expand the discussion of state training to research on aging—specifically, the link between resting state network activity, mindfulness training, and executive functioning.